Konstitusionalitas Ancaman Pidana Terhadap Kejari (Penetapan Status Barang Sitaan dan Prekursor Narkotika) - Emir Ardiansyah; Ulya Kencana; Romli SA (Wajah Hukum, 2021)
Studies on the constitutionality of criminal threats against the Attorney General's Office (Head of the State Prosecutor's Office) in determining the status of confiscated narcotics and narcotic precursors, based on the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics, it is very necessary to do so. The regulation has an over-criminalization nuance that is detrimental to the constitutional rights of the Kejari. The research aims to analyze the role of the state in protecting the constitutional rights of the Kejari within the rule of law framework. The scope of the research describes the structure of values or norms in statutory regulations and the principles it adheres to. Legal principles are used in interpreting the Narcotics Law by linking it to the rule of law framework. The research method is normative legal research using secondary data. The results of the research revealed that the provisions in Article 141 and Article 91 paragraph (1) of the Narcotics Law have the potential to violate the constitutional rights of the Kejari. because it is not in accordance with the protection of constitutional rights in the institutional structure of the prosecutor's office, which may not be intervened in criminal law enforcement. In conclusion, the state plays a major role in implementing the protection of the constitutional rights of citizens and Kejari officials. The state is obliged to fulfill, respect and protect the constitutional rights of citizens. Institutionally, the state synergizes with the prosecutor's office must affirm the ethical and administrative areas concretely and limitatively, so as not to cause obscurity of norms and excessive criminalization of non-criminal acts to become criminal acts.